Retribution - Esmail, Amani Ali (Journal of Islamic Sciences, 2021)
Retribution is the punishment of the intentional perpetrator with the same action which is the focus of our research, which is the killing of one life for one life, and God Almighty has prescribed it to protect society because of its relationship to the security system and without it, chaos and turmoil would take place.The research aims to enlighten Muslims about retribution, show the mercy and pleasure of Islam, clarify the reasons that prevent retribution after it is obligatory or its nullification. The researcher used the inductive approach in this research. The field of research is the jurisprudence of felonies, penalties, and retribution.This study showed that there are conditions for retribution that must be fulfilled and observed. The holy Qur’an, the Sunnah and consensus impose retribution and, its requirements, its nullification, the wisdom of instituting retribution, blood money if necessary, and pardon may be due to blood money or may be free.Islam also considers conditions that obstruct retribution, such as the absence of requirements of retribution or reconciliation. Islam has urged pardon, which indicates the tolerance of Islam.
Keywords: retribution; requirements for retribution; nullifiers for retribution; blood money